Experimental and theoretical studies of sandwich beams made of steel, concrete, and steel have shown interesting results. - shivakoti, deepika; VINOD, KUMAR G (The journal of contemporary issues in business and government, 2020)
Steel plates are subjected to axial and shear stresses to test theories of full and partial contact. Stud connections and frictional forces between steel plates and concrete at both the supports and load sites are included in the partial interaction research. Based on the partial interaction theory, the results of DSC beam testing are compared to the theoretical predictions. According to the findings, a theoretical approach may be used confidently to analyse fundamentally supported DSC beams of any shape. Various building techniques are described by terminology like "sandwich beams," "double skin composite structure," and "shear connections."